Mycoflora diversity in the stands and plantations of poplars in the section Aigeiros - Keča Nenad (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2004)
The saprophytic and parasitic fungi were inventoried in poplar stands and plantations in Serbia. During the four-year study, the material was collected from different localities in order to assess the density distribution and significance of individual fungal organisms occurring in the plantations on different clones and cultivars, but also in other stands of native poplars in the section Aigeiros.